Dampak Normalisasi Hubungan Israel dan Negara-Negara Arab Terhadap Isu Israel-Palestina - Rachmawati, Tety; Lestari, Rahayu; Fadhlillah, Nibras (Jurnal ICMES, 2025)
Normalization of relations with Israel by several Arab countries is referred to as an effort to help Palestine resolve its conflict with Israel. By establishing diplomatic relations, these Arab countries aim to become direct mediators for Palestinian independence. This study will attempt to examine the impact of the normalization of relations between Arab countries and Israel on the Palestinian issue. The research method employed is qualitative, utilizing a literature review. The researchers employ Keohane and Nye's concept of economic interdependency to analyze the relations between several Arab countries and Israel. The results of the study indicate that the normalization of relations between several Arab countries and Israel will only strengthen Israel's dominance in the Middle East due to the economic interdependency of Arab countries on Israel and the United States.